(untitled) (International Journal of Smart Agriculture, 2023)
The proximate composition and storage stability of selected bakery products from composite wheat-sologold sweet potato flour (40:60) were investigated. This is crucial to harness the beneficial attributes of the composite flour coupled with the quality of its baked products. Results of the proximate composition of the baked products (bread, biscuit and cake) from composite wheat-sologold sweet potato flour were as follows: moisture content (10.60, 8.20, 6.80%), crude fiber (0.42, 0.38, 0.40%), ash content (1.20, 1.40, 1.30%), protein content (17.10, 16.50, 18.40%), oil extract (5.83, 5.33, 5.30%) and nitrogen free extract (64.85, 66.79, 67.80%) respectively. These values are within the range of good quality marketable baked products. During storage under room temperature, the total bacterial and fungi count of the baked products were found to be within was within the tolerable limit of edible food. The wheat-sologold sweet potato is therefore, a potential composite flour in the baking industry for improved quality and safety of baked products.